Bispecific antibody does not induce T-cell death mediated by chimeric antigen receptor against disialoganglioside GD2 - Hoseini, Sayed Shahabuddin (Oncoimmunology, 2017)
Chimeric antigen receptors (CAR) and bispecific antibodies (BsAb) are two powerful immunotherapy approaches for retargeting lymphocytes toward cancer cells. Despite their success in lymphoblastic leukemia, solid tumors have been more recalcitrant. Identifying therapeutic barriers facing CAR-modified (CART) or BsAb-redirected T (BsAb-T) cells should facilitate their clinical translation to solid tumors. Novel lentiviral vectors containing low-affinity or high-affinity 4-1BB second-generation anti-GD2 (disialoganglioside) CARs were built to achieve efficient T cell transduction. The humanized anti-GD2 × CD3 BsAb using the IgG-scFv platform was described previously. CART and BsAb-engaged T cells were tested for viability, proliferation, and activation/exhaustion marker expression, and in vitro cytotoxicity against GD2(+) tumor cells. The antitumor effect of CAR-grafted and BsAb-T cells was compared in a human melanoma xenograft model. The majority of high CAR density T cells were depleted upon exposure to GD2(+) target cells while the BsAb-T cells survived. The in vitro cytotoxicity of the surviving CART cells was inferior to that of the BsAb-T cells. Using low-affinity CARs, inclusion of the 4-1BB co-stimulatory domain or exclusion of a co-stimulatory domain, or blocking PD1 did not prevent CART cell depletion. Both CART cells and BsAb-T cells penetrated established subcutaneous human melanoma xenografts; while both induced tumor regression, BsAb was more efficient. The fate of T cells activated by BsAb differs substantially from that by CAR, translating into a more robust antitumor effect both in vitro and in vivo.